Peranan Account Officer dalam Penanganan Less than Container Load Export pada PT. Masaji Kargosentra Tama di Belawan - Muhammad Firza Yafi; Taruna Taruna; Fadiyah Hani Sabila (Jurnal Riset dan Inovasi Manajemen, 2023)
Less than Container Load is a shipping service using containers where the sender of goods in one full container consists of several combined senders. The Less than Container Load shipping service allows the sender to spend lower costs because the shipping costs will be shared with other senders. The Less than Container Load load will be sent to the storage warehouse which will then be collected according to the destination country until it meets the quota in the stuffing process into the container. PT. Masaji Kargosentra Tama is engaged in domestic warehousing services and Container Freight Station export - import which has quite complete facilities to support activities such as storage warehouses, mechanical and non-mechanical loading and unloading equipment container yards, and container depots to facilitate export and import activities. The methods used in writing this final assignment are the field method (Field Research) and the library method (Library Research).